Pengaruh Desain Kemasan dan Pengiriman Produk Pecah Belah terhadap Keputusan Pembelian Konsumen di Perusahaan Jeeahomeware - Mario Ananda Viegas Simamora; Ronda Deli Sianturi; Dwi Pertiwi Anggraini (Social Science Academic, 2024)
This study aims to determine the influence of packaging design and delivery of glassware products on consumer purchase decisions at Jeeahomeware. The research method uses a quantitative approach with multiple linear regression analysis techniques. The research sample of 96 respondents was obtained through the purposive sampling method with the criteria of having bought Jeeahomeware glassware products at least twice in the last three months. The results of the partial test (t test) showed that the packaging design had a significant effect on the purchase decision with a t-value of 3.331 > t table 1.984 and a significance of 0.001 < 0.05. The delivery variable of glassware products also had a significant effect with t calculated 4.880 > t table 1.984 and significance 0.000 < 0.05. The results of the simultaneous test (F test) showed that F calculated 40.843 > F table 3.09 with a significance of 0.000 < 0.05, which means that the two variables together had a significant effect on the purchase decision. A determination coefficient value (R²) of 0.471 indicates that 47.1% of the variation in purchasing decisions can be explained by packaging design and product delivery, while 52.9% is influenced by other factors outside of this study. The conclusion of this study is that the packaging design and delivery of glassware products have a positive and significant effect, both partially and simultaneously, on consumer purchasing decisions at Jeeahomeware. Improving packaging quality and delivery reliability is expected to be able to encourage buying interest and consumer loyalty.